In vivo acute toxicity and mutagenic analysis of crude saponins from Chenopodium quinoa Willd husks. Issue 8 (26th January 2021) - Lin, Bingjie; Qi, Xiao; Fang, Lei; Zhao, Lei; Zhang, Ruoyu; Jing, Jinjin; Zhang, Shujie; Yang, Xiushi; Hou, Zhaohua; Xue, Peng
Abstract : As a functional food factor, quinoa saponins are valuable as additives and in medical care, pharmaceutical development, cosmetics and other fields. Abstract : Background : As a functional food factor, quinoa saponins are valuable as additives and in medical care, pharmaceutical development, cosmetics and other fields. However, few studies have investigated the toxicity of saponins. The main purpose of this study was to evaluate the toxicity of crude saponins extracted from quinoa husks. Thus, acute toxicity and excretion experiments were carried out in rats. The Ames test, micronucleus test and mouse sperm aberration test were carried out in mice. Results : In the acute toxicity study, the obtained LD50 was more than 10 g per kg per bw for both sexes, the food intake of all rats decreased over a period of time, and some rats developed diarrhea. In the case of large-dose gavage, the saponin excretion time in rats was approximately four days. When the dosage was 10 mg kg −1, quinoa saponins were hydrolyzed into aglycone within 24 hours and excreted out of the body. The results of the mutagenicity experiment showed that saponins had no mutagenicity in mice. Conclusion : This work has demonstrated that quinoa saponins have limited acute toxicity effects, which provides a theoretical basis for their rational utilization.